Enhancing firm performance and sustainability through creativity-oriented HRM and quality management: the mediating role of commercialization in the IT sector - Adiguzel, Zafer; Sönmez Çakır, Fatma; Altay Morgul, Umran; Çakır, Fatma Sönmez (Emerald Group Publishing Ltd, 2025)
PurposeThe research examines the impact of creativity-oriented human resources management (HRM) and quality management (QM) on firm performance, social sustainability and environmental performance, focusing on the mediating role of commercialization.Design/methodology/approachData were collected from 527 experts based in Istanbul with at least 5 years of experience in the information technologies (IT) sector. The sample includes a demographic distribution according to age ranges and educational qualifications. Using a survey containing 47 scales, confirmatory factor analysis (CFA) and structural equation modeling (SEM) analyzes were conducted through Jamovi 2.3.28.FindingsThe results show that both creativity-oriented HRM and QM positively affect commercialization. In addition, commercialization positively affects firm performance, social sustainability and environmental performance, thus establishing a mediating role in the relationship between management practices and performance results.Research limitations/implicationsThe research is limited to the IT sector in Istanbul, Turkey, and may not be generalizable to other regions or sectors. Future research may expand geographic and sectoral coverage to confirm and extend these findings.Practical implicationsCompanies can leverage creative HRM and QM strategies not only to increase commercialization efforts but also to achieve superior firm performance, social sustainability and environmental outcomes. This highlights the strategic role of HR and quality initiatives in driving overall business success.Social implicationsIn the research, it is stated that creativity-oriented HR is important to promote human capital as an important driver of performance improvement, supported by the resource-based view (RBV) theory. Also, by supporting the dynamic capabilities theory, by promoting quality and creativity, innovations can be better commercialized and both performance outcomes and sustainability results can be positively affected.Originality/valueThis research provides new insights into the mediating effects of commercialization between internal management practices and broad performance measures in the IT sector. It underlines the importance of promoting innovative HR and quality practices to achieve sustainable business performance.
Keywords: Creativity; Human Resources Management; Quality Management; Commercialization; Firm Performance; Social Sustainability; Environmental Performance